EVALI Vaping Liquids Part 2: Mass Spectrometric Identification of Diluents and Additives - Ciolino, Laura A.; Falconer, Travis M.; Ranieri, Tracy L.; Brueggemeyer, Jana L.; Taylor, Allison M.; Mohrhaus, Angela S. (Frontiers in Chemistry, 2021)
The vaping liquid additive vitamin E acetate (VEA) was strongly linked to the 2019 US nationwide outbreak of pulmonary lung illness (EVALI) associated with e-cigarettes or vaping liquids. Our laboratory received over 1000 vaping liquid products for identification of the vaping liquid additives, including hundreds of vaping products from EVALI patients. In this work, we present results obtained for the GC-MS identification of numerous vaping liquid additives in a large subset of ca. 300 Cannabis vaping liquids, including vitamin E acetate, medium chain triglycerides oil (MCT oil), polyethylene glycols, squalane, triethyl citrate, dipropylene glycol dibenzoate (DPG dibenzoate), pine rosin acids, pine rosin methyl esters, and sucrose acetate isobutyrate (SAIB). Confirmation of DPG benzoate and SAIB using LC-HRMS is also presented. GC-MS analysis for additives identified as the parent compounds was conducted after separation on a commercial 5% phenyl phase. GC-MS analysis for additives identified as the trimethylsilyl derivatives was conducted after separation on a commercial 35% silphenylene phase. LC-HRMS analysis was conducted using gradient elution with either C18 or phenyl-hexyl phases and determination of exact masses for the target compounds. In addition to providing rapid methods for the identification of vaping liquid additives, this work highlights the variety of Cannabis vaping liquid additives in current use.